INVESTIGATING THE PREVALENCE OF CARPAL TUNNEL SYNDROME IN OFFICE WORKERS - NASIR, N; MASOOD, I; NASIR, A; IKRAM, A; ZAFAR, A; AFZAL, F (Biological and Clinical Sciences Research Journal, 2024)
The widespread use of advanced technology and gadgets has led to numerous health problems, including wrist pain due to Carpal Tunnel Syndrome (CTS). CTS is a common and costly issue among office workers. Although research indicates that CTS is not inherently related to work, it is a work-related neuropathy resulting from the compression of the median nerve due to repetitive stressful wrist postures, such as hyperextension or hyperflexion. Objective: This study aims to measure the prevalence of Carpal Tunnel Syndrome (CTS) among office workers, considering computer usage and typing as risk factors, and to assess how job demands contribute to CTS at the workplace. Methods: A quantitative research model using a prospective survey design was employed. The study was conducted among office workers from the manufacturing and services industries in Punjab, Pakistan. A convenient sample of 280 office workers participated. Data were collected using the standardized Boston Carpal Tunnel Syndrome Questionnaire to evaluate the impact of CTS on activities of daily living (ADLs) and socioeconomic life. The study duration was six months. Data analysis was performed using SPSS software version 23.0. Results: The study found a comparatively high prevalence of work-related wrist and hand complaints, including clinically proven CTS, among youthful office employees in Pakistan. Regular discomfort while working significantly increased the likelihood of developing CTS. Extended periods of computer use without breaks also heightened the risk of wrist and hand symptoms. Conclusion: There is a significant prevalence of CTS among office workers in Pakistan linked to prolonged computer use and repetitive wrist postures. Effective interventions and ergonomic practices are essential to reduce the incidence and impact of CTS in the workplace.